A preface on advances in diagnostics for infectious and parasitic diseases: detecting parasites of medical and veterinary importance. Issue 14 (December 2014) - STOTHARD, J. RUSSELL; ADAMS, EMILY
SUMMARY: There are many reasons why detection of parasites of medical and veterinary importance is vital and where novel diagnostic and surveillance tools are required. From a medical perspective alone, these originate from a desire for better clinical management and rational use of medications. Diagnosis can be at the individual-level, at close to patient settings in testing a clinical suspicion or at the community-level, perhaps in front of a computer screen, in classification of endemic areas and devising appropriate control interventions. Thus diagnostics for parasitic diseases has a broad remit as parasites are not only tied with their definitive hosts but also in some cases with their vectors/intermediate hosts. Application of current diagnostic tools and decision algorithms in sustaining control programmes, or in elimination settings, can be problematic and even ill-fitting. For example in resource-limited settings, are current diagnostic tools sufficiently robust for operational use at scale or are they confounded by on-the-ground realities; are the diagnostic algorithms underlying public health interventions always understood and well-received within communities which are targeted for control? Within this Special Issue (SI) covering a variety of diseases and diagnostic settings some answers are forthcoming. An important theme, however, throughout the SI is to acknowledge that cross-talk and continuous feedback between development and application of diagnostic tests is crucial if they are to be used effectively and appropriately.